2012
DOI: 10.1051/fruits/2012034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the physicochemical and textural properties of pomelo fruit following storage

Abstract: -Introduction. Because of the long transportation times and storage durations that are often experienced, it is important to understand how pomelo properties change over time; that will be indicative of how long samples can be stored before they drop below acceptable quality limits. As no information is available regarding storage of pomelo fruit in the literature, the goal of our work was to study the change in pomelo physicochemical and textural properties following storage over a period of approximately 4 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Figure presents the effects of the applied treatments on color parameters and their comparison with the control fruits during the evaluated storage time. The luminosity L * increased, the green index −a * decreased, and the yellow index +b * increased when the storage time increased, which has been reported previously by Sirisomboon and Lapchareonsuk for pomelo fruits . The L * value of the grapefruits that underwent HWT was larger than the L * value of control grapefruits; on the other hand, grapefruits that underwent MW‐HWT exhibited a similar L * value to control grapefruits.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…Figure presents the effects of the applied treatments on color parameters and their comparison with the control fruits during the evaluated storage time. The luminosity L * increased, the green index −a * decreased, and the yellow index +b * increased when the storage time increased, which has been reported previously by Sirisomboon and Lapchareonsuk for pomelo fruits . The L * value of the grapefruits that underwent HWT was larger than the L * value of control grapefruits; on the other hand, grapefruits that underwent MW‐HWT exhibited a similar L * value to control grapefruits.…”
Section: Resultssupporting
confidence: 82%
“…The firmness fell after 16 days of storage, losing the good quality of the fruits. Previous studies had reported that the flavedo firmness of pomelo ( Citrus grandis ), a fruit similar to grapefruit, decreased as the storage time increased because the cells beneath the skin became weaker following the storage . Analyzing the results with storage time as a co‐variable, the treatments applied have no effect on the firmness of the grapefruits ( P > 0.05).…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Traditional pomelo internal quality detection methods include sensory [6] and physicochemical index methods [7,8], both of which are time-and labor-intensive, damage and waste fruit, and cannot be applied to detect and guarantee the quality of every postharvest pomelo. Machine vision has been widely applied as a fast, intelligent, and nondestructive method for grading fruit quality [9,10], but this only provides information concerning external characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from research done on physicochemical and textural properties of pomelo (Sirisomboon and Lapchareonsuk 2012;Sirisomboon and Theamprateep 2012), sensory profile studies of the fruit are limited. In the study by Cheong et al (2011), aroma profiles of the peel and blossoms of two Malaysian pomelo cultivars were evaluated.…”
Section: Introductionmentioning
confidence: 99%